Effect of Different Rates of Nitrogen Fertilization on Crop Yield, Soil Properties and Leaf Physiological Attributes in Banana Under Subtropical Regions of China - Sun, Jianbo; Li, Wenbin; Li, Chunqiang; Chang, Wenjun; Zhang, Shiqing; Zeng, Yanbo; Zeng, Changying; Peng, Ming (Frontiers in Plant Science, 2020)
Optimum nitrogen (N) fertilizer management is necessary for enhancing soil quality and crop productivity. We conducted a field experiment to evaluate the effect of nitrogen fertilization rates on physiological parameters (chlorophyll, plant metabolic enzymes, soluble matters) of banana leaves, soil properties (soil enzymes, soil organic matter (SOM), soil available nutrients) and banana crop yield in a subtropical region of southern China. We tested N application rates of 0 (N0), 145 (N145), 248 (N248), 352 (N352), 414 (NFT) and 455 (N455) g N per plant. The correlations among soil factors, leaf physiological factors and crop yield were evaluated. The results indiated that the high rates of N fertilization (NFT and N455) significantly decreased soil available potassium (K) content, available phosphorus (P) content, glutamine synthetase (GS) activity, and soluble protein and sugar contents compared with lower N rates. Factor analysis showed that the N352 treatment had the highest integrated score for soil and leaf physiological factors among all treatments. Moreover, the N352 treatment was the most effective in improving carbon and nitrogen metabolism in banana. Crop yield was significantly and positively linearly correlated with the integrated score (r = 0.823, P < 0.05). Path analysis revealed that invertase, SOM and sucrose synthase (SS) had a strong positive effect on banana yield. Canonical correspondence analysis (CCA) suggested that available K, invertase, acid phosphatase and available P were the most important factors impacting leaf physiological parameters. Cluster analysis demonstrated distinct differences in N application treatment related to variations in soil and leaf factors. This study suggested that lower N rates, particularly 352 g N per plant (N352) were more effective in improving crop yield by enhancing the soil quality and leaf physiological parameters than higher rates of N fertilization and local farmers’ practice.